Further Remarks On Somewhere Dense Sets - Arwini, Khadiga; Mira, Huda Almqtouf (Journal of Pure & Applied Sciences, 2022)
In this article, we prove that a topological space X is strongly hyperconnected iff any somewhere dense set in X is open, in addition we investigate some conditions that make sets somewhere dense in subspaces, finally, we show that any topological space defined on infinite set X has SD-cover with no proper subcover.